Histopathology and microscopic morphology of protozoan and metazoan parasites of free ranging armadillos in Brazil - Alexandre Arenales; Estevam G.L. Hoppe; Chris Gardiner; Juliana P.S. Mol; Karin Werther; Renato L. Santos (Pesquisa Veterinária Brasileira, 2021)
ABSTRACT: This study assessed microscopic morphology of protozoan and metazoan parasites, as well as parasite-associated histopathologic changes in five Brazilian free-ranging armadillos. Three armadillos had intra sarcolemmal cysts of Sarcocystis sp. in skeletal muscles without microscopic changes. One Dasypus novemcinctus was found parasitized with a nematode morphologically compatible with an oxyurid in the small intestine. One Dasypus sp. had neutrophilic enteritis associated with adult and larval stages of Strongyloides sp. and one D. novemcinctus had multiple embryonated eggs free in the lumen of the small intestine with mild neutrophilic enteritis. These findings represent a contribution for expanding our knowledge on parasitic diseases of armadillos.